AMALGAMATED N P S FERTILIZER ON CROP PERFORMANCE AND NODULATION OF SOYBEAN VARIETIES ON ACIDIC SOIL. - Tesfa Imenu; Tolera Abera; Kinde Lamessa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This experiment was aimed to evaluate the effect of amalgamated NPS chemical fertilizer on crop performance and nodulation of soybean (Glycine max L (Merrill)) varieties on acidic soil during 2020 cropping season. Varieties of soybean i.e “Katta” and “Korme” and six levels of amalgamated NPS chemical fertilizer were used in factorial arrangement within randomized complete block design with three replications. Nodule parameters were highly influenced (P